Modeling of a fluidized bed propylene polymerization reactor operated in condensed mode - Utikar, Ranjeet P.; Harshe, Yogesh M.; Mehra, Anurag; Ranade, Vivek V. (Journal of Applied Polymer Science, 2008)
The gas-phase polymerization of propylene is one of the most widely accepted and commercially used processes for the manufacture of polypropylene (PP). Because of the highly exothermic nature of polymerization reactions, temperature runaway and subsequent polymer melting and agglomeration may occur, and the reactor has to be operated in a small operating window for safety. The addition of liquid monomer for heat removal (condensed mode) broadens the operating window and can substantially increase (by 50-100%) the capacity of given reactor hardware. This article describes the extension of a comprehensive mathematical model for the simulation of fluidized bed PP reactors to include the condensed mode of operations. The model is used to determine the influence of the operating parameters on the polymer properties and particle size distribution. The model is also used to determine the effects of two active sites and the reaction kinetics on macroscopic variables. The developed framework is useful for simulating multimonomer, multisite Ziegler-Natta-type olefin fluidized bed polymerization reactors operated under condensed mode. (C) 2008 Wiley Periodicals, Inc. J Appl Polym Sci 108: 2067-2076, 2008.
Keywords: Modeling; Polyolefins; Ziegler-Natta polymerization

Processing of TGA data: analysis of isoconversional and model fitting methods - Jain, Ankit A.; Mehra, Anurag; Ranade, Vivek V. (Fuel, 2016)
Thermogravimetric analysis (TGA) is routinely used to characterize coal. Apart from proximate analysis, TGA data is also used to characterize kinetics of devolatilization and char combustion. Various methods have been proposed to process the TGA data [isoconversional or model free methods such as Friedman method, Kissinger method, Flynn-Wall-Ozawa method (FWO), Kissinger-Akahira-Sunose method (KAS) or single or multi-reaction models (SRMs/MRMs) and distributed activation energy models (DAEMs)]. In this work, we have critically examined various models for processing TGA data obtained with typical Indian coal. A generalized equation has been proposed to encompass different models as special cases. We have also considered a model based on a possibility of distribution of frequency factor along with constant or distribution of activation energies. The results of TGA data described by different models were critically analyzed. The presented results and methodology will be useful for selecting appropriate strategy for processing TGA data. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: DAEM; High ash coal; Isoconversional methods; Pyrolysis; TGA